1995
DOI: 10.1007/bf02187757
|View full text |Cite
|
Sign up to set email alerts
|

Relative risk of deterioration after mild closed head injury

Abstract: In this prospective study, a series of 1812 consecutive mild head injured adult patients who visited the hospital emergency department were assessed. Twenty-eight patients (1.5%) deteriorated after head injury; 23 of these (1.3% of the series) required surgical intervention. Five patients (0.3%) deteriorated due to non-surgical causes [post-traumatic seizure 2, syndrome of inappropriate secretion of antidiuretic hormone (SIADH) 3]. Most of the deterioration occurred within the first 24 hours (57%). Post-trauma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 32 publications
0
18
1
2
Order By: Relevance
“…25) Many studies have reported increased risk of intracranial lesions in patients with head injury aged over 65 years 9,29) or over 60 years. 2,4,5,7,16,24,34) Aging is one risk factor, but it is unlikely that there is a specific age threshold above which the risk suddenly increases. 24) Analysis of our subjects aged over 65 years old found no significant difference in lesion frequency, but risk does seem to become higher at around 60 years.…”
Section: Ct Indications In Mild Head Injurymentioning
confidence: 99%
“…25) Many studies have reported increased risk of intracranial lesions in patients with head injury aged over 65 years 9,29) or over 60 years. 2,4,5,7,16,24,34) Aging is one risk factor, but it is unlikely that there is a specific age threshold above which the risk suddenly increases. 24) Analysis of our subjects aged over 65 years old found no significant difference in lesion frequency, but risk does seem to become higher at around 60 years.…”
Section: Ct Indications In Mild Head Injurymentioning
confidence: 99%
“…This presented a quandary, initially resulting in misdiagnosis and improper treatment. The only other head-injury-related reports available in the literature describe patients sustaining head injury severe enough to cause skull fractures, intracranial hematomas, subarachnoid hemorrhages, and/or Glascow coma scale scores of < 12 [7][8][9][10]. Our patient had none of these findings, and without severe head injury, SIADH was not initially considered as a cause of his hyponatremia.…”
Section: Discussionmentioning
confidence: 69%
“…A 68-year-old female with closed head injury from a motor vehicle accident, having a skull fracture, subdural hematoma, subarachnoid hemorrhage and cerebral contusions, manifested SIADH with asymptomatic hyponatremia and without clinical deterioration [9]. In a study of 1,812 consecutive patients with mild closed head injury, only two developed hyponatremia, and both of these patients had documented intracranial hemorrhage [10]. In a similar study of 1,808 patients with head injury, 0.6% of 842 patients defined as having mild head injury, developed SIADH [11].…”
Section: Discussionmentioning
confidence: 99%
“…9 Alguns autores sugerem, em casos de vômitos e cefaleia pós-TCE, a realização de TC e internação para observação, por provável lesão cerebral. 7,10 Nee et al 11 demonstraram que a presença de VPTCE aumenta em quatro vezes o risco de fratura de crânio em pacientes alertas, sem diferenças entre crianças e adultos. Outros autores defendem que o vômito como sintoma isolado não predispõe a riscos de lesão cerebral grave.…”
Section: Introductionunclassified
“…12 Apesar de todas as controvérsias, é consenso entre os autores que o número de episódios de vômito não aumenta a predisposição à lesão intracraniana, assim um simples episódio não seria mais importante que vários. 5,10,12 Os autores apresentam sua experiência com crianças, vítimas de traumatismo cranioencefálico leve, e discutem sobre a presença de vômitos e sua associação com o prognóstico do paciente. A presença de vômitos em pacientes com TCE leve em alguns serviços é um dos requisitos usados pelos médicos para indicação de TC.…”
Section: Introductionunclassified